Development and psychometric testing of an instrument to measure safety climate perceptions in community pharmacy. Issue 6 (31st October 2014) - Newham, Rosemary; Bennie, Marion; Maxwell, David; Watson, Anne; de Wet, Carl; Bowie, Paul
Abstract Rationale, aims and objectives A positive and strong safety culture underpins effective learning from patient safety incidents in health care, including the community pharmacy (CP) setting. To build this culture, perceptions of safety climate must be measured with context‐specific and reliable instruments. No pre‐existing instruments were specifically designed or suitable for CP within Scotland. We therefore aimed to develop a psychometrically sound instrument to measure perceptions of safety climate within Scottish CPs. Methods The first stage, development of a preliminary instrument, comprised three steps: (i) a literature review; (ii) focus group feedback; and (iii) content validation. The second stage, psychometric testing, consisted of three further steps: (iv) a pilot survey; (v) a survey of all CP staff within a single health board in NHS Scotland; and (vi) application of statistical methods, including principal components analysis and calculation of Cronbach's reliability coefficients, to derive the final instrument. Results The preliminary questionnaire was developed through a process of literature review and feedback. This questionnaire was completed by staff in 50 CPs from the 131 (38%) sampled. 250 completed questionnaires were suitable for analysis. Psychometric evaluation resulted in a 30‐item instrument with five positively correlated safety climate factors: leadership, teamwork, safety systems, communication and working conditions. Reliability coefficients were satisfactory for the safety climate factors (α > 0.7) and overall (α = 0.93). Conclusions The robust nature of the technical design and testing process has resulted in the development of an instrument with sufficient psychometric properties, which can be implemented in the community pharmacy setting in NHS Scotland.